2019
DOI: 10.1002/cae.22087
|View full text |Cite
|
Sign up to set email alerts
|

A distributed case‐ and project‐based learning to design 3D lab on electronic engineering education

Abstract: Recently, virtual laboratories have popping up in online learning for students to self‐enroll in the experiments. Like in‐class teaching methodology, virtual laboratories need to meet the requirements as same as real world laboratories and support efficient learning and communication services. In this paper, we detail the development of our distributed 3D lab system based on case‐and project‐based learning method, which support semi‐automatic experiment creation, assessment and knowledge‐based instant conversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In addition, in terms of coping styles, the symptomatic nursing for patients enabled them to face death directly and improve the courage and confidence of treatment. Therefore, the scores of various coping styles in the EG after intervention were better than those in the CG ( P < 0.05), which was consistent with the study of Yang et al [ 25 ]. The project teaching method simulates the clinical nursing team management so that nurses can quickly adapt to work.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, in terms of coping styles, the symptomatic nursing for patients enabled them to face death directly and improve the courage and confidence of treatment. Therefore, the scores of various coping styles in the EG after intervention were better than those in the CG ( P < 0.05), which was consistent with the study of Yang et al [ 25 ]. The project teaching method simulates the clinical nursing team management so that nurses can quickly adapt to work.…”
Section: Discussionsupporting
confidence: 90%
“…Several PBL experiences at the university level in the scope of computer applications in engineering education have been considered in the past. In Reference [18], a distributed 3D lab system was based on PBL method, supporting knowledge‐based instant conversation and semi‐automatic experiment creation. Similarly, in Reference [9], an innovative PBL approach using an FPGA‐based tool to teach image processing algorithms was presented.…”
Section: Methodsmentioning
confidence: 99%
“…Since the initial introductions of the VL concepts, research on the effectiveness of VLs confirmed that properly designed virtual simulation tools can enhance students' learning processes [9], [10]. As a result, VLs have been implemented and/or studied across the wide variety of disciplines, such as life science (e.g., biology) [11], [12], [13], [14], [15], physical sciences (e.g., physics and chemistry) [16], [17], [18], [19], [20], mathematics/computer sciences [21], [22], [23], [24], [25], and engineering [26], [27], [28], [29], [30]. However, we will need to be careful when using the term "virtual lab" since there is no set definition for "virtual lab."…”
Section: Literature Reviewmentioning
confidence: 99%